Democratic Republic of the Congo : Staff Report for the 2009 Article IV Consultation, Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Request for Additional Interim Assistance Under the Enhanced Initiative for Heavily Indebted Poor Countries. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses a Request from Congo for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) program. Growth in Congo in 2008 was strong, but weakened by the onset of the global financial crisis during the second half of the year that resulted in a deterioration of the country's terms of trade and large job losses in the mining sector. Macroeconomic policies for the rest of 2009 and 2010 aim at reducing inflation while mitigating the impact of the global financial sector on the economy.